Pengaruh Persepsi Keamanan dan Persepsi Manfaat Melalui Sikap Terhadap Niat Penggunaan Ulang QRIS Oleh Generasi Z Kota Mataram - Mirna Agustina (Postgraduate, University of Mataram, 2025)
This study aims to analyse the effect of perceived security and perceived benefits on the intention to reuse Quick Response Code Indonesian Standard (QRIS) by Generation Z in Mataram City, with attitude as a mediation variable. The method used is a quantitative survey with data collection through questionnaires distributed to 150 respondents who are active users of QRIS. Data analysis was done using structural equation modelling (SEM) with SmartPLS software. The results showed that perceived security and perceived benefits have a positive and significant influence on QRIS reuse intentions. In addition, attitude is found to act as a mediation that strengthens the relationship between perceived security and benefits on reuse intentions. These findings indicate that Generation Z in Mataram City are very concerned about the security and benefits aspects of using QRIS. Therefore, service providers need to increase education and promotion that emphasises the safety and benefits of QRIS to encourage wider adoption among the younger generation. This study provides important insights for the development of marketing strategies and improvement of digital payment services in Indonesia.